TGF-β1 Signaling: Immune Dynamics of Chronic Kidney Diseases - Tang, Philip Chiu-Tsun; Chan, Alex Siu-Wing; Zhang, Cai-Bin; García Córdoba, Cristina Alexandra; Zhang, Ying-Ying; To, Ka-Fai; Leung, Kam-Tong; Lan, Hui-Yao; Tang, Patrick Ming-Kuen (Frontiers in Medicine, 2021)
Chronic kidney disease (CKD) is a major cause of morbidity and mortality worldwide, imposing a great burden on the healthcare system. Regrettably, effective CKD therapeutic strategies are yet available due to their elusive pathogenic mechanisms. CKD is featured by progressive inflammation and fibrosis associated with immune cell dysfunction, leading to the formation of an inflammatory microenvironment, which ultimately exacerbating renal fibrosis. Transforming growth factor β1 (TGF-β1) is an indispensable immunoregulator promoting CKD progression by controlling the activation, proliferation, and apoptosis of immunocytes via both canonical and non-canonical pathways. More importantly, recent studies have uncovered a new mechanism of TGF-β1 for de novo generation of myofibroblast via macrophage-myofibroblast transition (MMT). This review will update the versatile roles of TGF-β signaling in the dynamics of renal immunity, a better understanding may facilitate the discovery of novel therapeutic strategies against CKD.